PEMBERDAYAAN MASYARAKAT MELALUI PENDATAAN PENDUDUK BERBASIS WEB SIG (STUDI KASUS KELURAHAN KAMBU KOTA KENDARI) - Anita Puspita Dewi; Henny Henny (semanTIK, 2016)
Geographic Information Systems  (GIS) are generally associated with a map. On the map, the information contained within may vary, according to the manufacturer or user requirements. Along with the development of digital media and forms of its communications, GIS applications are also growing more and more accessible and easier for the spread of information. The design of the map is displayed in the system using Google Maps, the software used in building this application is PHP as the programming language, and MySQL as a database server. So with the use of all such design, the system can establish a geographic and demographic conditions in the Kambu Village of Kendari City and also can empower  the communities by how the public can enter and edit its own data as well as the location of their family's home. With the help of this website is expected to help facilitate the users to fulfill their information requirements. In this system, it can display the data along with the location of residential population as well, population statistics were obtained from the data that has been entered so that much easier for the residents and village to find and search the population data. The system also provides information about the profile of Kambu Village as well as the vision and mission. Keywords— GIS, Website, Google Maps, Kambu Village